Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1158/1538-7445.sabcs18-gs4-07
|View full text |Cite
|
Sign up to set email alerts
|

Abstract GS4-07: Race, ethnicity and clinical outcomes in hormone receptor-positive, HER2-negative, node-negative breast cancer: results from the TAILORx trial

Abstract: Background: Black race is associated with worse outcomes in localized hormone receptor (HR)-positive breast cancer in population-based and in clinical trial cohorts, whether using self-identified race (Albain et al. JNCI 2009 [PMID: 19584328; Sparano et al. JNCI 2012 [PMID: 22250182) or genetically-identified race (Schneider et al. J Precision Oncol 2017 [PMID: 29333527]). This disparity persists after adjustment for treatment delivery parameters (Hershman et al. JCO 2009 [PMID:19307504]). We evaluated clinico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The distribution of Oncotype DX scores did not differ significantly between black and white women in our study (P = .9). This is consistent with the data presented by Albain et al 36 at the 41st Annual San Antonio Breast Cancer Symposium (December 4-8, 2018; San Antonio, Texas), which consisted of race-stratified results from the Trial Assigning Individualized Options for Treatment (TAILORx) and showed that although recurrence scores were similar in black and white women, despite comparable adjuvant systemic therapy, black women had worse outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…The distribution of Oncotype DX scores did not differ significantly between black and white women in our study (P = .9). This is consistent with the data presented by Albain et al 36 at the 41st Annual San Antonio Breast Cancer Symposium (December 4-8, 2018; San Antonio, Texas), which consisted of race-stratified results from the Trial Assigning Individualized Options for Treatment (TAILORx) and showed that although recurrence scores were similar in black and white women, despite comparable adjuvant systemic therapy, black women had worse outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…Molecular assays (eg, a loss of heterozygosity) are more reliable approaches for showing clonal relationships between original tumors and ipsilateral IBCs and for distinguishing genetically related recurrences from genetically distinct new primaries. Using commonly used definitions of intermediate (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and high recurrence risks (≥31) generated a similar result. The 21-gene recurrence score is an assay based on reverse transcription-polymerase chain reaction that is currently applied to early-stage, ER+ IBC to assess the prognosis and the likely benefit from chemotherapy in addition to endocrine therapy.…”
Section: Discussionmentioning
confidence: 63%
“…29 Using the TAILORxdefined cutoff value of 26,19 we observed that black patients with DCIS were more likely than white counterparts to subsequently develop aggressive ER+ IBC. Using commonly used definitions of intermediate (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and high recurrence risks (≥31) generated a similar result. This finding was consistent with the racial difference in RNA expression-based recurrence scores reported for first primary IBC.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations